The association analysis polymorphism of CDKAL1 and diabetic retinopathy in Chinese Han population - Liu, Nai-Jia (Int J Ophthalmol, 2016)
AIM: To identify the contribution of CDKAL1 to the development of diabetic retinopathy (DR) in Chinese population. METHODS: A case-control study was performed to investigate the genetic association between DR and polymorphic variants of CDKAL1 in Chinese Han population with type 2 diabetes mellitus (T2DM). A well-defined population with T2DM, consisting of 475 controls and 105 DR patients, was recruited. All subjects were genotyped for the genetic variant (rs10946398) of CDKAL1. Genotyping was performed by iPLEX technology. The association between rs10946398 and T2DM was assessed by univariate and multivariate logistic regression (MLR) analysis. RESULTS: There were significant differences in C allele frequencies of rs10946398 (CDKAL1) between control and DR groups (45.06% versus 55.00%, P<0.05). The rs10946398 of CDKAL1 was found to be associated with the increased risk of DR among patients with diabetes. CONCLUSION: Our findings suggest that rs10946398 of CDKAL1 is independently associated with DR in a Chinese Han population.